2021
DOI: 10.1590/1678-4162-12284
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity and mortality in Holstein calves from birth to 145 days of age on a large dairy farm in Brazil

Abstract: The present study aimed to investigate the morbidity and mortality associated with the most common diseases during the rearing period of Holstein calves in a high-production dairy farm. The calves (n = 600) were allocated to three groups based on age: G1 (1-7 days, n = 216), G2 (30-40 days, n = 188), and G3 (69-85 days, n = 196). They were evaluated over 60 days at eight different times. The morbidity rates were 47.67% (286/600) for diarrhea, 73.00% (438/600) for bovine respiratory disease (BRD), and 3.83% (23… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
0
3
1
1
Order By: Relevance
“…With this new method of classification, the prevalence of positive results for WISC for all farms was 30% (145/482). This prevalence is lower than the frequency of 73% (438/600) observed in our previous research, in which a positive WISC was defined by a total respiratory score ≥4, which included suspect and positive animals (Gomes et al, 2021). This apparent difference in prevalence reported by the same research team in the same country demonstrates the importance of clinical score definition on estimates of disease prevalence.…”
Section: Discussioncontrasting
confidence: 72%
See 2 more Smart Citations
“…With this new method of classification, the prevalence of positive results for WISC for all farms was 30% (145/482). This prevalence is lower than the frequency of 73% (438/600) observed in our previous research, in which a positive WISC was defined by a total respiratory score ≥4, which included suspect and positive animals (Gomes et al, 2021). This apparent difference in prevalence reported by the same research team in the same country demonstrates the importance of clinical score definition on estimates of disease prevalence.…”
Section: Discussioncontrasting
confidence: 72%
“…Evaluation of these data indicated that the rectal temperature was the main parameter responsible for the positive Wisconsin score when the initial classification proposed by McGuirk (2008) was used, in which a positive score was defined as a total score of 5 or greater. In this previous research, the distribution of rectal temperatures according to the Wisconsin score was (number and percentage of total): 679 (13.57%), 1,738 (34.75%), 2,258 (45.15%), and 326 (6.51%) from a total of 5,001 observations, for scores of 3, 2, 1, and 0, respectively (Gomes et al, 2021). Based on these previous results, we formulated the hypothesis that the relatively high temperatures seen in calves could be related to differences in environmental conditions and weather in tropical or subtropical countries versus Wisconsin, and that this could invalidate the use of the Wisconsin scoring system or the California scoring system, which was developed based on the Wisconsin system.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In various European surveys, dairy calf mortality ranged from 2.0 to 8.0% [6,[11][12][13]. In Brazil, these values were more variable, ranging from 2.33% [14] to 18.79% [15]. Thus, there is an urgent need to review dairy calf management methods and as an initial step, to evaluate animal welfare under various kinds of management [2].…”
Section: Introductionmentioning
confidence: 99%
“…De acordo com dados do padrão ouro de criação de bezerras, a meta de prevalencia de diarreia e pneumonia em bezerras de até 60 dias de vida deve ser inferior a 15,0 e 10,0%, respectivamente, e a mortalidade inferior a 3,0 % (DCHA, 2016). Pesquisa realizada no Brasil no estado de São Paulo mostrou que a morbidade na fase de aleitamento é de 47,6% para diarreia, 73,0% para doença respiratória e 3,8% para inflamações umbilicais, a taxa de mortalidade foi de 2,3% (GOMES et al, 2021). Dados do relatório da Alta Cria trazem informações de 135 propriedades de leite localizadas em diferentes estados brasileiros, o relatório mostra que a taxa de mortalidade de bezerras durante o aleitamento foi de 6%, estando correlacionada com a eficiência na colostragem, propriedades com colostragem excelente apresentaram 4% de taxa de mortalidade, enquanto propriedades com colostragem ruim tiveram taxa de mortalidade de 8% (ALTA CRIA, 2021).…”
Section: Introductionunclassified